Social Network Analysis of EduTubers - Pasquel-López, Cynthia; Rodríguez-Aceves, Lucía; Valerio-Ureña, Gabriel (Frontiers in Education, 2022)
The popularity of educational videos has increased in recent years. In 2018, YouTube announced a $20 million investment to support educational video creators and organized the YouTube EduCon event to bring them together and form a community. The COVID-19 pandemic pushed educational institutions to use resources contained in public repositories, such as YouTube. The objective of this research study was to explore the dynamics of EduTubers to understand the motivations for their interactions. We used social network analysis (SNA) with YouTube data to analyze the dynamics of EduTubers’ recommendation networks. Meaningful insights reveal a relationship between the level of digital engagement and the level of out-degree. Additionally, we confirm that educhannel homophily has a positive effect on the level of reciprocity. The main contribution lies in the use of theoretical concepts (reciprocity and homophily), focusing on the intrinsic motivations of EduTubers to recommend other channels. The practical implications of the results suggest that educhannels that initiate and grow digital engagement are more likely to participate in a recommendation network.